‘Glocalization of Politics’ in South Asia and Central Asia 2012-2016 - Nabeela Akbar; Rana Eijaz Ahmad (Journal of Political Studies, 2016)
The Central Asia and South Asia have become pivotal in the contemporary global politics. The closing of the twentieth century and the beginning of the twenty-first century have developed complex political conditions in the region due to changed geo-political circumstances which has involved South Asia and Central Asia as well. The object of the paper is to analyze that the’ Glocalization of politics’ in South Asia and Central Asia focuses on the concept of thinking global and acting local. It my overcome a complex of geopolitical, logistical, and economic factors which are a barrier in interregional connectivity and to transport the natural resources of Central Asian states to the global market in order to meet the world’s growing energy demands. Though Central Asia has abundant of natural resources, yet its geopolitical conditions have made it difficult for transporting and marketing them to the world economic market. The main problem that foreign investors are facing in the Central Asia is that how to transport the energy reservoirs from these landlocked states to the world market. The transportation route is of great geopolitical significance. The regional and global actors are in pursuit of their own national interests and to get politico-economic benefits from these two strategically important regions. The presence of regional and global competitors has aggravated the affairs of both regions. The research methodology is descriptive and analytical and the conclusion of this research paper is that the’ Glocalization of politics’ in South Asia and Central Asia is inversely proportional to the inter-regional connectivity.